ANALISIS PELAKSANAAN PUTUSAN PENGADILAN AGAMA MAROS KELAS 1B TENTANG NAFKAH TERUTANG SUAMI TERHADAP ISTRI DALAM PERSPEKTIF MAQASHID ASY-SYARIA (Studi Kasus : putusan No. 374/Pdt.G/2024/PA.Mrs) - Kamra, Syamsul; Syarifuddin Abu Baedah, Said; Syahid, Akhmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of the Maros Class 1B Religious Court’s decision regarding the payment of outstanding maintenance (nafkah terutang) from a husband to his wife, viewed from the perspective of maqāṣid al-sharī‘ah. The decision in Case No. 374/Pdt.G/2024/PA.Mrs stipulated the husband’s obligation to pay iddah maintenance, mut‘ah, and outstanding maintenance. However, the decision has not been carried out by the defendant, and the plaintiff has not filed an application for execution. The research adopts a descriptive qualitative approach, employing interviews, documentation, and juridical analysis. The findings indicate that factors supporting the implementation of the decision include the clarity of the ruling, the realistic amount of maintenance awarded, and the availability of legal aid services. On the other hand, the main obstacles consist of the plaintiff’s limited legal knowledge, the defendant’s uncooperative attitude, and various administrative and psychological barriers.From the perspective of maqāṣid al-sharī‘ah, the decision substantively reflects the protection of wealth (ḥifẓ al-māl), life (ḥifẓ al-nafs), and honor (ḥifẓ al-‘irḍ). Nevertheless, its non-implementation demonstrates that the objectives of maqāṣid have not been fully achieved. Therefore, reforms in the enforcement system are necessary to ensure that substantive justice can be realized for those entitled to it. Keywords: Decision, Maintenance Owed, Maqashid Al-Syariah